The Effect of Emotional Intelligence and Spiritual Intelligence on Juvenile Delinquency of Vocational School - Esterina, Meriam; Kusumastuti , Wanodya; Novitasari, Putri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Adolescents as the nation's successors need to develop a positive attitude that can support the progress of the nation. Negative adolescent behavior such as juvenile delinquency can harm both oneself and the environment and society. This study aims to see the influence of emotional intelligence and spiritual intelligence on juvenile delinquency. This research is quantitative research with a survey method conducted on 115 vocational school students of Purworejo. Data were analyzed using the multiple regression method with SPSS 21.00. The results showed that there was an influence between emotional and spiritual intelligence on juvenile delinquency.